A 4-year follow-up study of 20 cases of stable localized childhood vitiligo treated by autologous, noncultured melanocyte-keratinocyte cell transplantation - Ettappurath N Abdul Latheef; S. Rahima; K. Muhammed; Najeeba Riyaz (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo is a common skin disease affecting 1% to 2% of general population. Even though different modalities of treatment available, it remains as a difficult disease to treat. Many cases remain stable after a period of medical therapy without any further response. For treating pediatric vitiligo, currently available and result providing therapies are limited. Surgical techniques are the only hope in such patients. Only limited studies are available regarding surgical interventions in childhood vitiligo. Aim: To evaluate the response of autologous, noncultured melanocyte-keratinocyte cell transplantation in childhood stable vitiligo. Methods: A retrospective analysis was conducted in 20 cases of stable localized childhood vitiligo (10 segmental and 10 focal) treated by autologous, noncultured melanocyte-keratinocyte cell transplantation. Serial photographs were taken from the first visit onwards. The patients were followed for a period of 4 years. The results were analyzed on a visual analog scale. Results: Out of total 20 cases, 11 had excellent (90-100%) response, 4 had good (60-89%), 2 had fair (25-59%), and 3 had poor response (0-24%). Age and sex of the patients and size and duration of lesions did not show significant influence on results of transplantation. Conclusion: This is a simple, safe, and effective surgical therapy for replenishing the missing melanocytes even in resistant cases of vitiligo. Only limited studies are there in childhood vitiligo. In spite of its invasive nature, it can be used to treat localized stable vitiligo in children.